The gene spectrum of thalassemia in Yangjiang of western Guangdong Province - Liang, Hong-Feng; Liang, Wei-Min; Xie, Wen-Guang; Lin, Fen; Liu, Li-Li; Li, Lie-Jun; Ge, Yi-Yuan; Lu, Min; Liao, Yu-Wei; Zeng, Guang-Kuan; Yao, Jin-Xiu; Situ, Jing-Wei; et al. (Frontiers in Genetics, 2023)
Background: Thalassemia presents a higher incidence in southern China. The objective of this study is to analyze the genotype distribution of thalassemia in Yangjiang, a western city of Guangdong province in China. Methods: The genotypes of suspected cases with thalassemia were tested by PCR and reverse dot blot (RDB). Unidentified rare thalassemia genotypes of the samples were further ascertained by PCR and direct DNA sequencing. Results: Among 22467 suspected cases with thalassemia, 7658 cases were found with thalassemia genotypes by our PCR-RDB kit, 5313 cases were α-thalassemia (α-thal) alone, --SEA/αα was the most common genotype, accounting for 61.75% of α-thal genotypes, and the following mutations were -α3.7/αα, -α4.2/αα, αCSα/αα, αWSα/αα, and αQSα/αα. 2032 cases were β-thalassemia (β-thal) alone, βCD41-42/βN, βIVS-II-654/βN, and β-28/βN accounted for 80.9% of all β-thal genotypes, and the following genotypes were βCD17/βN, βCD71-72/βN, and βE/βN. 11 cases of compound heterozygotes of β-thal and 5 cases of β-thalassemia homozygotes were identified in this study. 313 cases were identified with α-thal combined with β-thal, showing 57 genotype combinations of the coincidence of both Hb disorders, one extreme patient had a genotype of --SEA/αWSα and βCD41-42/β-28. In addition, 4 rare α mutations (--THAI, HKαα, Hb Q-Thailand, CD31 AGG>AAG) and 6 rare β mutations (CD39 CAG>TAG, IVS-Ⅱ-2 (-T), -90(C>T), Chinese Gγ+(Aγδβ)0, CD104(-G), and CD19 A>G) were also found in this study population. Conclusions: This study provided detailed genotypes of thalassemia in Yangjiang of western Guangdong province of China, reflected the complexity of genotypes in this high prevalent region, and this would be valuable for diagnosis and counseling for thalassemia in this area.